Implicações e desdobramentos de uma direção compartilhada: apontamentos a partir de um processo de criação em modo colaborativo conduzido por três encenadoras (Revista NUPEART, 2021)
Among the many possibilities opened by the way of organizing artists in a collaborative creative process, there is the challenge of developing a staging sharing the director's role. The present work proposes to analyze a creative exercise developed in curricular components in a university context, problematizing crossings observed in a collaborative process directed by three directors. Faced with a shared staging, considerations about the director's actions are presented, highlighting the implications and possibilities that the shared function can reveal. As a theoretical apparatus, there is an approach to the studies of Fagundes (2009, 2016) and Fischer (2003), among other authors, to deepen the relations on poetic, ethical and political aspects of the director's work.
Keywords: Staging; Collaborative Process; Postdramatic theatre